Determinant of Trust in the Bank and Attitudes on Technology of Mobile Banking - Kurniawati ,Desy Ratna Sari (International Journal of Advanced Science and Technology, 2020)
The objective of this study was to evaluate the antecedents and consequences of attitudes towards Mobile Banking adoption to facilitate daily banking transactions. This study focuses on three M-Banking (Mobile Banking) of government banks that are included in the top brand index category. The method that is used to collect the sample was non probability sampling with purposive sampling technique. Bank Mandiri, BRI, BNI consumers who used the Mobile  Banking services with three times minimum transactions in the last three months in the Jabodetabek area were the sample of the conducted research. The number of samples used was 275 respondents, in which respondents were asked to fill out a questionnaire. The SEM with AMOS 22.0 program was used as an analytical tool for this study. The results of this study showed that Perceived Reliability and Perceived Privacy positively influenced Trust in the bank. Perceived Usability, Perceived Practicality, Trust in the Bank, Perceived Enjoyment, and Consumer Innovativeness positively influenced Attitudes, and Attitudes positively influenced Intentions. To conclude the data that has been researched and showed, the bank needs to be more aware of the reliability of M-Banking technology performance, and privacy of Consumers who use M-Banking to convince Consumers about privacy issues. Moreover, bankers also needs to build characteristics of Consumer innovativeness to be more open to utilize advanced technologies such as M-Banking.